Poder de uma micro-influenciadora de lifestyle na mudança do comportamento dos seguidores no Instagram e Youtube - Almeida, Bruna Daniela Tavares de (2021)
The power of a digital influencer on multiple digital platforms is very important for all digital marketing entities. It is increasingly evident that consumers trust the opinions and advice of common people more than the brands themselves. Therefore, micro-influencers are a strong bet of communication agencies and brands, standing out for their genuineness and transparency towards their followers. The main objective of the present investigation is to provide an overview of the power of a lifestyle micro-influencer in changing the behavior of followers on Instagram and Youtube. In order to achieve this goal, we chose to use a mixed research method, which combines the application of qualitative and quantitative techniques. As part of the qualitative method, interviews were conducted, one of them in the form of a focus group, to collect the views of the three essential elements involved in the influence marketing ecosystem, the digital micro-influencer, its followers and an agency of Communication. In the quantitative method, Instagram and Youtube statistics of the micro-influencer under study were collected. The results obtained allowed to conclude that a lifestyle micro-influencer can induce and change the habits and behaviors in the lives of her followers in a positive and genuine way, demonstrating that she can be more trustworthy than many macro-influencers.